Allergy and sports - Patriarca, G.; Pecora, V. (Medicina dello Sport, 2012)
Allergic disease, especially allergy involving the upper and lower airways (rhinitis and bronchial asthma) are widely thought to restrict participation in sports. Even against a background of a growing incidence of allergy worldwide, highest in the developed countries, such beliefs are disproved by clinical evidence and pose a relational and psychological barrier to engaging in sports, particularly among the young. What epidemiological data tell us about elite competitive athletes is that, when adequately managed, allergy, and bronchial asthma in particular, does not restrict sports participation. Among the athletes competing in the 2008 Olympic Games in Beijing, about 25% were affected by rhinitis and 17% by allergic bronchial asthma.